1992
DOI: 10.1523/jneurosci.12-06-02403.1992
|View full text |Cite
|
Sign up to set email alerts
|

A parsimonious description of motoneuron dendritic morphology using computer simulation

Abstract: Most quantitative descriptions of neuronal dendrite morphology involve tabulations of measurements and correlations among them. The present work is an attempt to extract from such data a parsimonious set of parameters that are sufficient to describe the quantitative features of individual and pooled dendrites, including their statistical variability. A relatively simple stochastic (Monte Carlo) model was devised to simulate branching dendritic trees. The necessary parameters were then derived directly from mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 20 publications
2
86
1
Order By: Relevance
“…This method relies on developing stochastic growth models for the dendrites and axons of both MSNs and FSIs. For the dendritic trees, we used an existing growth algorithm (Burke et al, 1992) and found its parameters using a genetic algorithm search of a fitness space defined by known parameters (e.g. number of branch points) of the neuron type's dendritic tree.…”
Section: The Neuroanatomical Modelmentioning
confidence: 99%
“…This method relies on developing stochastic growth models for the dendrites and axons of both MSNs and FSIs. For the dendritic trees, we used an existing growth algorithm (Burke et al, 1992) and found its parameters using a genetic algorithm search of a fitness space defined by known parameters (e.g. number of branch points) of the neuron type's dendritic tree.…”
Section: The Neuroanatomical Modelmentioning
confidence: 99%
“…To distinguish between these connotations, some investigators have adopted the term ''stem dendrite'' to describe a primary dendrite and all of its branches (e.g., Rose, 1981). However, the same term has frequently been used as a substitute for primary dendrite (e.g., Kernell and Zwaagstra, 1989;Burke et al, 1992). To avoid this confusion, we have adopted the term ''primary subtree'' to describe a primary dendrite and all of its branches (cf.…”
Section: Reconstruction Of Dendritic Trees and Data Analysismentioning
confidence: 99%
“…In a recent study, Burke et al (1992) have searched for a parsimonious description of motoneuron morphology by using computer simulations based upon empirically measured distribution functions for several morphological parameters, including the lengths and diameters of dendritic branches. Such a description was given in terms of probability functions needed for the stochastic reconstruction of the dendrites, and ''included two processes, one for generating (the length of) individual branches, given their proximal diameters, and the second for selecting proximal diameters for the daughter branches produced at dichotomous branching points.''…”
Section: Interpretation Of Parametersmentioning
confidence: 99%